Employee Control and Discipline: Patterns and Priorities - Dimick, David (Relations industrielles / Industrial Relations, 1978)
This study is directed to the issue of what determines the importance of an offence. Two types of characteristics were examined: the offence itself and several aspects of the organizations involved. It is possible to compare some of the results obtained here with a survey of U.S. compares (BNA, 1973).